2010
DOI: 10.1007/s11664-010-1142-3
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Reduction of HgCdTe/Si Through Ex Situ Annealing

Abstract: Current growth methods of HgCdTe/Cd(Se)Te/Si by molecular-beam epitaxy (MBE) result in a dislocation density of mid 10 6 cm À2 to low 10 7 cm À2 . Although the exact mechanism is unknown, it is well accepted that this high level of dislocation density leads to poorer long-wavelength infrared (LWIR) focal-plane array (FPA) performance, especially in terms of operability. We have conducted a detailed study of ex situ cycle annealing of HgCdTe/ Cd(Se)Te/Si material in order to reduce the total number of dislocati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…10,11 The temperatures reported in previous works were in reference to the set-point of the furnace, as an accurate temperature calibration was not known at the time. Since the publication of those articles, the actual sample temperature has been calibrated from the furnace set-points, as explained in the ''Experimental Procedures'' section.…”
Section: Dislocation Reductionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,11 The temperatures reported in previous works were in reference to the set-point of the furnace, as an accurate temperature calibration was not known at the time. Since the publication of those articles, the actual sample temperature has been calibrated from the furnace set-points, as explained in the ''Experimental Procedures'' section.…”
Section: Dislocation Reductionmentioning
confidence: 99%
“…We previously reported that, for temperatures greater than 500°C, the EPD reduces to 1 9 10 6 cm À2 after four or more cycles. 10,11 Closer inspection of TCA performed at 550°C revealed that EPD saturation can be expected after two or three cycles of annealing. At a lower temperature of $450°C we find that it requires 16 cycles to reduce the EPD to the 1 9 10 6 cm À2 level.…”
Section: Dislocation Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 It has been demonstrated that this higher dislocation level results in lower device performance, especially in the LWIR regime. 2 There is ongoing effort within the community to either reduce dislocations in HgCdTe/Si or render the dislocations electrically inactive, [3][4][5][6] but to date no single approach yields material with dislocation density values or device performance similar to those of HgCdTe grown on bulk lattice-matched substrates. Without use of scalable and relatively inexpensive substrates, the development of third-generation IRFPAs using Hg-based compounds is severely hindered as large format sizes and cost are major drivers for future systems.…”
Section: Introductionmentioning
confidence: 99%